Elimination of Disera Application Needs as an Online Booking Application for Android-Based Motorcycle Services in Mataram City Using Survey and Prototyping Techniques - Muhammad Ari Rifqi; Deni Saputra; Sri Anggraini; Heri Wijayanto (LPPM Universitas Qamarul Huda Badaruddin, 2024)
One of the businesses in the service sector that is needed by the community who use motorbikes is a repair shop. The existence of workshops scattered in areas in the city of Mataram often causes people to be confused about finding a workshop that suits their needs. Based on the existing problems, a solution was designed, namely Disera (Digital Service App). DISERA is a service-based digital business to connect automotive experts or repair workers with people who need motorcycle service services. In the DISERA application development process, a structured requirements identification technique is needed. Based on the presentation of the problem and the urgency of elicitation, this research will focus on how to identify the need for the DISERA application as an Android-based motorcycle online service ordering application in the city of Mataram. The elicitation techniques that will be used in this study are survey and prototyping techniques with the aim of obtaining actual user needs and providing prototype designs so that the application development process becomes more focused and produces a good appearance. This research was conducted using a mix of methods, namely qualitative and quantitative methods. Quantitative methods are used as a scheme in collecting data in the form of numbers from survey results to selecting data from observations. While the qualitative method is constructed as a correlative scheme in analyzing problems in the results of case studies and reviewing the basic theory of concept development. In the application design process, data collection is first carried out from primary data obtained through digital surveys, so that user data is obtained to determine the application development process. Prototyping techniques in the software requirements elicitation process can help the process of making application designs that suit user needs. The result is that through survey and prototyping techniques can create application designs that meet user needs